The US Census longitudinal employer-household dynamics datasets - Robert Manduca (REGION, 2018)
Over the last several years, the Longitudinal Employer-Household Dynamics program at the US Census Bureau has partnered with state labor market information offices to produce a collection of extremely rich datasets based on linked employer-employee records. These datasets, available free for download from the program website, offer~exceptionally detailed information on a number of topics of interest to regional scientists, including migration, local labor market dynamics, and the spatial distribution of employment. This article describes the process by which these data are generated, the different publicly available datasets, and examples of research in regional science that is already using these data.
Keywords: 330